Full Genome Sequence and sfRNA Interferon Antagonist Activity of Zika Virus from Recife, Brazil - Donald, Claire L; Brennan, Benjamin; Cumberworth, Stephanie L; Rezelj, Veronica V; Clark, Jordan J; Cordeiro, Marli T; Freitas de Oliveira França, Rafael; Pena, Lindomar J; Wilkie, Gavin S; Da Silva Filipe, Ana; Davis, Christopher; Hughes, Joseph; et al. (PLoS neglected tropical diseases, 2016)
BACKGROUND: The outbreak of Zika virus (ZIKV) in the Americas has transformed a previously obscure mosquito-transmitted arbovirus of the Flaviviridae family into a major public health concern. Little is currently known about the evolution and biology of ZIKV and the factors that contribute to the associated pathogenesis. Determining genomic sequences of clinical viral isolates and characterization of elements within these are an important prerequisite to advance our understanding of viral replicative processes and virus-host interactions. METHODOLOGY/PRINCIPAL FINDINGS: We obtained a ZIKV isolate from a patient who presented with classical ZIKV-associated symptoms, and used high throughput sequencing and other molecular biology approaches to determine its full genome sequence, including non-coding regions. Genome regions were characterized and compared to the sequences of other isolates where available. Furthermore, we identified a subgenomic flavivirus RNA (sfRNA) in ZIKV-infected cells that has antagonist activity against RIG-I induced type I interferon induction, with a lesser effect on MDA-5 mediated action. CONCLUSIONS/SIGNIFICANCE: The full-length genome sequence including non-coding regions of a South American ZIKV isolate from a patient with classical symptoms will support efforts to develop genetic tools for this virus. Detection of sfRNA that counteracts interferon responses is likely to be important for further understanding of pathogenesis and virus-host interactions.
Keywords: A549 Cells; infekce virem zika; Vero Cells; Brazil; Disease Outbreaks; RNA, Viral; Zika Virus Infection; Host-Pathogen Interactions; replikace viru; epidemický výskyt choroby; zvířata; Humans; interferon typ I; genom virový; Zika Virus; interakce hostitele a patogenu; High-Throughput Nucleotide Sequencing; fylogeneze; Brazílie; vysoce účinné nukleotidové sekvenování; DEAD box protein 58; Interferon Type I; DEAD Box Protein 58; virus zika; buňky A549; Phylogeny; Virus Replication; Vero buňky; RNA virová; Genome, Viral; lidé; Animals